2003
DOI: 10.1002/hlca.200390240
|View full text |Cite
|
Sign up to set email alerts
|

A Sensitive and Selective High‐Throughput Screening Fluorescence Assay for Lipases and Esterases

Abstract: Long-chain fatty acid esters of 7-(3,4-dihydroxybutyloxy)-2H-1-benzopyran-2-one (6) such as octanoate 2a are shown to be exceptionally sensitive and selective fluorogenic substrates for lipases and esterases. Umbelliferone (8) is released upon hydrolysis of the ester function in 2a in the presence of bovine serum albumin and sodium periodate. These substrates are at least by one order of magnitude more sensitive to lipases than the commercial fluorogenic substrate 4-methylumbelliferyl heptanoate. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 23 publications
2
20
0
Order By: Relevance
“…Moreover depending on conditions the magnitude of the effect is different, and in some cases even accidental contact of 4-MOU with alkaline solution can significantly deteriorate analytical usefulness of substrate. It should be stressed that degradation of coumarin derivatives has been previously demonstrated by Nyfeler, et al [3]. In this work it was observed that commercially available 4-methylumbelliferone acyl esters spontaneously hydrolyze at pH 8.8 and higher.…”
Section: Spontaneous Hydrolysis Of 4-muo (In Microspheres and In Solusupporting
confidence: 61%
See 1 more Smart Citation
“…Moreover depending on conditions the magnitude of the effect is different, and in some cases even accidental contact of 4-MOU with alkaline solution can significantly deteriorate analytical usefulness of substrate. It should be stressed that degradation of coumarin derivatives has been previously demonstrated by Nyfeler, et al [3]. In this work it was observed that commercially available 4-methylumbelliferone acyl esters spontaneously hydrolyze at pH 8.8 and higher.…”
Section: Spontaneous Hydrolysis Of 4-muo (In Microspheres and In Solusupporting
confidence: 61%
“…This effect was observed, e.g. for coumarines derivatives used as substrates [1][2][3]. Occurrence of spontaneous decomposition, especially priori analysis, can result in false elevated results of determination; affecting also the sensitivity of determination.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, the functional group reacting with the enzyme is non -activated and therefore much less prone to uncatalyzed spontaneous hydrolysis in the assay medium. The Clips -O substrate 19 is particularly reactive with lipases because the enzyme reactive ester is part of a 1,2 -diol monoester function resembling the natural glyceride ester substrates of these enzymes [33] .…”
Section: The Clips -O Substrates With Periodatementioning
confidence: 99%
“…They used a chiral secondary alcohol linked to an umbelliferone with an ether bond; this was oxidized to the corresponding ketone by alcohol dehydrogenase, then treatment with bovine serum albumin (BSA) released the fluorescent product by b-elimination. [8] This technique was later adapted for variety of different enzymes, such as lipases, esterases, [9] aldolases, [10] amidases, [11] phosphatases, [12] epoxide hydrolases, [13] and Bayer-Villiger monooxygenases. [14] Various enzymes were examined, and activity was detected as a timedependent increase in fluorescence intensity.…”
Section: Introductionmentioning
confidence: 99%